2013
DOI: 10.1016/j.bcp.2013.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivities of the vascular KATP channel to various PPAR activators

Abstract: Several agonists of the peroxisome proliferator-activated receptors (PPARs) are currently used for the treatment of metabolic disorders including diabetes. We have recently shown that one of them, Rosiglitazone, inhibits the vascular ATP-sensitive K+ (KATP) channel and compromises the coronary vasodilation by the β-adrenoceptor agonist. Here, we show evidence for the channel inhibition by various PPAR agonists, information that may be useful for finding new therapeutical agents with less cardiovascular side-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies have been conducted to determine the mechanisms by which the activated PPARβ/δ induces vasodilation in arteries, possibly mediated by direct interaction with RhoA [8,14], activation of PI3-Akt-eNOS pathways [15] or activation of K + channels [16]. In order to address the question as to whether PPARβ/δ directly interferes with the RhoA/ROCK pathway and K + channels, we took advantage of the dilatory properties of the agonist GW0742.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been conducted to determine the mechanisms by which the activated PPARβ/δ induces vasodilation in arteries, possibly mediated by direct interaction with RhoA [8,14], activation of PI3-Akt-eNOS pathways [15] or activation of K + channels [16]. In order to address the question as to whether PPARβ/δ directly interferes with the RhoA/ROCK pathway and K + channels, we took advantage of the dilatory properties of the agonist GW0742.…”
Section: Resultsmentioning
confidence: 99%
“…are another class of drugs used clinically for the treatment of type 2 diabetes via their effect on peroxisome proliferator-activated receptors (PPARs) [ 125 ]. However, patch clamp experiments on HEK cells expressing various subtypes of K ATP channels have shown that these compounds also block vascular K ATP channels to various degrees [ 130 ]. Rosiglitazone was found to inhibit all isoforms of K ATP channels.…”
Section: Pharmacological Tools Targeting K Atp Cha...mentioning
confidence: 99%
“…Recently, signaling engaged after GPCR recruitment of β-arrestin proteins have emerged as new G protein-independent intracellular signaling pathways (Luttrell and Gesty-Palmer, 2010; Rajagopal et al, 2010a). To increase the complexity, a single GPCR has pleiotropic signaling properties and each signal can crosstalk at different levels with the transactivation of cell surface receptor having tyrosine kinase activity (EGF-R, PDGF-R, FGF-R, for examples) or serine/threonine kinase activity (TGF-β, for example) or with the formation of multimers, thus potentially influencing the signaling pathways of the different receptors (Burch et al, 2012; Wang and Lewis, 2013). Indeed, numerous biochemical and biophysical studies supports that GPCRs can form physiologically relevant homo-, hetero-, or oligo-mers (Angers et al, 2002).…”
Section: New Hopes To Overcome Undesired Effectsmentioning
confidence: 99%